Programmed Death-Ligand 1 (PD-L1) and Ki-67 Labeling Index: Correlation with Tumor Grade and Recurrence - Wildanur, Sri; Yenita; Mulyani, Henny (HM Publisher, 2025)
Background: Meningiomas are common primary brain tumors with variable clinical behavior. While most are benign, a subset exhibits aggressive characteristics and a high recurrence rate. This study aimed to investigate the association of Programmed Death-Ligand 1 (PD-L1) and Ki-67 labeling index with histopathological grade and recurrence in meningioma. Methods: A retrospective study was conducted on 139 cases of meningioma diagnosed between January 2020 and December 2023. PD-L1 expression was evaluated using immunohistochemistry (IHC) and scored using the combined positive score (CPS). Ki-67 labeling index was determined as the percentage of tumor cells with positive nuclear staining. The association of PD-L1 and Ki-67 with histopathological grade and recurrence was analyzed. Results: PD-L1 expression was positive in 66.7% of cases and was significantly associated with recurrence (p = 0.006). A higher Ki-67 labeling index (>4%) was observed in 68.9% of cases and was also significantly associated with recurrence (p = 0.013). No significant association was found between PD-L1 expression or Ki-67 labeling index and histopathological grade. Conclusion: PD-L1 expression and Ki-67 labeling index may serve as potential prognostic markers for predicting recurrence in meningioma. Further studies are needed to validate these findings and explore their potential therapeutic implications.